Efektivitas Pembiayaan Kesehatan Insentif UKM bagi Tenaga Kesehatan di Puskesmas Kabupaten Jayapura - Kurniawan, Adi; Assa, Inriyati (JURNAL EKOLOGI BIROKRASI, 2024)
This study aimed to assess the effectiveness of health financing for Community Health Efforts (CHE) incentives for health workers in improving the Essential Community Health Efforts program in Jayapura Regency. The research used a qualitative design with a case study approach. The analysis revealed that the health financing for CHE incentives at Puskesmas in Jayapura Regency is insufficient. This is due to the underutilization of budget and local regulations that govern the operation of health centers in the region. The main issue lies in the suboptimal incentives provided to health workers in the Puskesmas CHE program. The study suggests that interventions should be made by maximizing CHE incentives for Puskesmas staff for various reasons. Firstly, Puskesmas employees, especially field staff who work outside the health centers, play a crucial role in the CHE program. Secondly, by maximizing incentives, Puskesmas can effectively address problems related to human resource management, thus improving the performance of health organizations at the local level.